Gilt Management for Fertility and Longevity - Patterson, Jennifer (Animals (Basel), 2019)
SIMPLE SUMMARY: Improving sow lifetime productivity, herd stability, and maximizing lifetime performance and longevity in the sow herd, represent significant challenges to the swine industry. Routine implementation of efficient gilt development unit (GDU) programs which deliver high quality, breeding-eligible gilts to the sow farm is still needed. Good gilt management starts at birth, because litter of origin, lactation management and the application of early selection strategies are early indicators of future performance and efficiency. A failure to select gilts with the greatest reproductive potential and inappropriate management of their physiological state and metabolic condition at service, are key risk factors for poor sow lifetime productivity (SLP). Management practices that deliver gilts with the greatest potential SLP are crucial to the productivity of conventional production systems. ABSTRACT: Substantial evidence supports successful management of gilts as an absolutely necessary component of breeding herd management and the pivotal starting point for the future fertility and longevity of the breeding herd. Therefore, gilt management practices from birth have the potential to influence the future reproductive performance of the sow herd. A good gilt management program will address several key components such as birth traits that determine the efficiency of replacement gilt production; effective selection of the most fertile gilts for entry to the breeding herd; effective management programs that provide a consistent supply of service eligible gilts; and appropriate management of weight, physiological maturity, and a positive metabolic state at breeding. Good gilt management can largely resolve the existing gap between excellent genetic potential and the more modest sow lifetime productivity typically achieved in the industry. Investment in good gilt development programs from birth represents a foundational opportunity for improving the efficiency of the pork production industry.